Sintering effects on mechanical properties of biologically derived dentine hydroxyapatite - (:unkn) unknown (My University, 2002)
In this study, the change in the mechanical properties of hydroxyapatite (HA), which is the main mineral content of bone and teeth, commonly used as an implant material, is tested for different sintering temperatures. Although HA shows great biocompatibility with the human body, its applications are limited to non-load-bearing areas and coatings due to its low mechanical properties. These mechanical properties can be improved substantially by sintering. In this study, naturally produced HA from human teeth is sintered, and density, microhardness measurements and compression tests are performed in order to find the optimum sintering temperature. The results are compared with the synthetically derived HA properties from the literature. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: Hydroxyapatite; Sintering